Indwelling urinary catheters, aortic valve treatment and delirium: a prospective cohort study. Issue 11 (1st November 2018) - Eide, Leslie SP; Ranhoff, Anette H; Lauck, Sandra; Fridlund, Bengt; Haaverstad, Rune; Hufthammer, Karl Ove; Kuiper, Karel K J; Nordrehaug, Jan Erik; Norekvål, Tone Merete
Abstract : Objectives: To determine whether an association exists between delirium and length of time indwelling urine catheters (IUC) are used in octogenarian patients treated with surgical aortic valve treatment (SAVR) or transcatheter aortic valve implantation (TAVI). Design: Prospective cohort study. Setting: Tertiary university hospital covering the western region of Norway. Participants: Octogenarian patients undergoing elective SAVR or TAVI and willing to participate in the study were eligible. Patients unable to speak Norwegian were excluded. Between 2011 and 2013, 143 consecutive patients were included, and data from 136 of them are presented. Primary outcome: Delirium. Results: Logistic regression analysis shows that lower cognitive function was positively associated with delirium (OR 0.86, CI 0.74 to 0.99, p=0.047). Besides, the interaction term in the model shows that IUC use and delirium differed between SAVR and TAVI patients (p=0.04). The difference corresponded to a weaker association between hours of IUC use and delirium for SAVR (OR 1.01, CI: 0.99 to 1.03, p=0.54) compared with that for TAVI (OR 1.04, CI: 1.01 to 1.08, p=0.004). Conclusions: The association between IUC use and delirium is stronger for octogenarian patients treated with TAVI than for patients who received SAVR. Our results revealed a previously unknown association between the number of hours an IUC is used and postoperative delirium in octogenarian patients treated with TAVI.